The Effect of Vitrectomy Infusion Solutions on Postoperative Electroretinography and Retina Histology. Issue 1 (3rd April 2017) - AbdEl Dayem, Hisham; Hartzer, Michael; Williams, George; Ferrone, Philip
Abstract : Purpose: A prospective, randomised, masked study comparing three different intraocular infusion solutions used during vitrectomy on postoperative electroretinography (ERG) and retinal histology of rabbit eyes. Methods, materials and animals: Twelve rabbit eyes were used with each group of three intraocular infusion solutions: Lactated Ringers (LR), balanced salt solution (BSS) and balanced salt solution-plus (BSS-Plus). Results: At 24 hours postoperatively, the ERG values were 36%, 68% and 75% of the normal values for LR, BSS and BSS-Plus, respectively. At 72 hours postoperatively, the ERG values were 50%, 84% and 100% of the normal values for LR, BSS and BSS-Plus, respectively. At 72 hours postoperatively, 3/12, 10/12 and 12/12 of the vitrectomised eyes had regained normal-value ERGs for LR, BSS, and BSS-Plus eyes, respectively. At 1 week postoperatively, 4/12 and 12/12 of LR and BSS eyes, respectively, had normal ERGs. The number of LR eyes regaining normal ERG values was 4/12, 6/12 and 9/12, measured at 1, 4 and 15 weeks postoperatively, respectively. Retina histology: At 15 weeks follow-up, histopathology was performed on several rabbit eyes. Histological examination of LR-irrigated eyes showed 2/7 normal retinas, whereas 5/7 showed changes that ranged from vacuoles in the inner retina to numerous vacuoles in both the outer and inner retina with disruption of the inner nuclear layer. The histology of BSS-infused and BSS-Plus-infused rabbit eyes was normal. Conclusion: LR solution, when used during vitrectomy, has a more prolonged negative effect on ERG than BSS and BSS-Plus. Histological changes seen in LR eyes may explain the ERG results.